Federal Regulation of the Food Industry: Part 1, The Regulatory Process - Ronald H. Schmidt; Douglas L. Archer; Michael T. Olexa (EDIS, 2005)
This fact sheet is intended to enhance understanding of federal regulations and provide a general overview of the regulatory process. This document is FSHN05-10, one of a series of the Food Science and Human Nutrition Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date May 2005.